1990
DOI: 10.1111/j.1365-2621.1990.tb06010.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Oxidation in Chicken Muscles and Skin After Roasting and Refrigerated Storage of Main Broiler Parts

Abstract: The muscles and attached skin of fresh chicken broiler parts, which were roasted in a convection oven and subsequently kept at 4°C for 4 days were analyzed for lipid oxidation products (LOP). Roasting and refrigerated storage significantly increased the amount of malonaldehyde which occurred faster in the skin than in the muscles. Also, after roasting, lipid oxidation fluorescence products increased in the aqueous phase and, after refrigerated storage, in the organic phase of Folch extracted muscles and skin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The DHA levels reached 151.2 and 209.1 mg/100 g fw in roasted breast and leg fillets, with the respective total LC ω3 PUFA concentrations being 215.1 and 283.4 mg/100 g. The percent loss of ω3 LC PUFA during roasting was calculated to range between 6.7 and 12.1% in breast fillets and 28.5 and 39.6% in leg fillets ( Table 6). The lower loss of ω3 LC PUFA in roasted breast fillets, is in agreement with previous reports (Abrilm & Barclay, 1998), which attributed the lower DHA loss from poultry breast to its known lower fat and higher phospholipid content (Marion & Woodroof, 1965;Pikul & Kummerow, 1990). Additionally the higher fat loss during roasting of leg fillets (see previous session) could partly explain the lower retentions of DHA and the other LC ω3 PUFA.…”
Section: Roasted Samplessupporting
confidence: 89%
“…The DHA levels reached 151.2 and 209.1 mg/100 g fw in roasted breast and leg fillets, with the respective total LC ω3 PUFA concentrations being 215.1 and 283.4 mg/100 g. The percent loss of ω3 LC PUFA during roasting was calculated to range between 6.7 and 12.1% in breast fillets and 28.5 and 39.6% in leg fillets ( Table 6). The lower loss of ω3 LC PUFA in roasted breast fillets, is in agreement with previous reports (Abrilm & Barclay, 1998), which attributed the lower DHA loss from poultry breast to its known lower fat and higher phospholipid content (Marion & Woodroof, 1965;Pikul & Kummerow, 1990). Additionally the higher fat loss during roasting of leg fillets (see previous session) could partly explain the lower retentions of DHA and the other LC ω3 PUFA.…”
Section: Roasted Samplessupporting
confidence: 89%
“…Gardner (1979) has suggested that the fluorescent products are the Schiff bases that are produced from the interaction of lipid carbonyls and the protein-amino group present, although it remains possible that the fluorescent products may have derived from the reaction of oxygen radicals with proteins (Giulivi & Cadenas, 1993). Therefore, the level of fluorescent products present in water extracts of homogenate has been previously employed as an indicator of the extent of oxidation of flesh-contained proteins (Lin & Liang, 2002;Pikul & Kummerow, 1990). Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Since 1958 it was already noted that there were a number of factors influencing poultry edible meat cooking losses, including: degree of fatness; distribution of fat; postmortem stage; age; size, and cooking times [27]. The consistent increase in breast meat DHA upon cooking is probably due to its lower fat and higher phospholipid content [28]. Ackman et al [29] have previously demonstrated a 15% (w/w) decrease in phospholipid content in poultry white meat upon cooking and a 53% decrease in poultry dark meat phospholipids, consistent with our higher losses of DHA in the dark meat.…”
Section: Resultsmentioning
confidence: 99%